The Relationship between Social skills and Attitude towards Substance Abuse among High School Students - Mehri Ghobadi; Ehsan Kazemnezhad Leili; Masoumeh Jafari Asl; Seyedeh Zahra Shafipour (Guilan University of Medical Sciences, 2020)
Introduction: Substance abuse is one of the health, medical, and social problems in today's world that affects more or less all societies. Adolescence is one of the riskiest periods of life in terms of beginning high-risk behaviors such as drug use. Objective: This study aimed to determine the relationship between social skills and attitudes towards substance abuse in high school adolescents in Rasht City, Iran. Materials and Methods: In this analytical cross-sectional study, 750 male and female high school students in the 10th, 11th, and 12th grades of Rasht City in north of Iran were selected and examined using the cluster sampling method. Data collection tools included a demographic information questionnaire, a social skills questionnaire, and the addiction potential scale. The collected data were analyzed using the Spearman, Mann-Whitney, Kruskal-Wallis correlation tests, and logistic regression model. Results: In the study, 51.1% of subjects aged 16-17 years, 57.7% were girls, 85.2% of them lived with their parents, and 82.9% of the students stated that there is no addict in their family. Based on the results, the Mean±SD score of social skills in students was 271.05±23.73. In various subscales of social skills, 62% to 73.9% of students were able to obtain a mean or upper grade. The students' highest skill was related to the decision-making subscale with the Mean±SD score of 28.90±3.76 and the lowest was related to coping with stress with the Mean±SD of 25.47±4.40. Also, regarding the attitude towards drug abuse, the highest Mean±SD score (more positive attitude towards drug abuse) was related to the subscales of drug use effects (2.68±0.90); and the lowest Mean±SD (more negative attitude towards drug abuse) was related to the subscale of drug use or the tendency to use drugs (2.14±1.02). According to the results, there was a significant reverse relationship between the mean±SD social skills and attitudes scores towards substance abuse (r=-0.442, P<0.001). The findings also showed that gender is considered as a predictor variable of substance abuse attitudes, so that boys were 1.36 times more positive than girls (OR: 1.36, 95% CI=0.980-1.900, P<0.066). Conclusion: Based on the results, social skills training to increase self-efficacy and selfconfidence in dealing with life's challenges and problems may have long-term effects in preventing the occurrence of high-risk behaviors such as substance abuse and creating the right attitude in them.